2013
DOI: 10.1105/tpc.113.118018
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Cardiolipin Synthase for Mitochondrial Ultrastructure, Respiratory Function, Plant Development, and Stress Responses in Arabidopsis

Abstract: Cardiolipin (CL) is the signature phospholipid of the mitochondrial inner membrane. In animals and yeast (Saccharomyces cerevisiae), CL depletion affects the stability of respiratory supercomplexes and is thus crucial to the energy metabolism of obligate aerobes. In eukaryotes, the last step of CL synthesis is catalyzed by CARDIOLIPIN SYNTHASE (CLS), encoded by a single-copy gene. Here, we characterize a cls mutant in Arabidopsis thaliana, which is devoid of CL. In contrast to yeast cls, where development is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 87 publications
10
71
1
Order By: Relevance
“…Atcls mutants harbor some of the features of yeast and mammal CL-deficient cells, such as low abundance of CI/CIII supercomplexes and abnormal mitochondria with few cristae. 16,17 Moreover giant mitochondria were observed suggesting deficiency of the plant mitochondrial fusion/fission machinery, 16,17 confirming previous results obtained in animals and yeast. [18][19][20] More specifically it was found that CL plays a dominant role in mitochondrial fission through the major mitochondrial fission factor, DYNAMIN-RELATED PROTEIN3 (DRP3).…”
supporting
confidence: 78%
See 3 more Smart Citations
“…Atcls mutants harbor some of the features of yeast and mammal CL-deficient cells, such as low abundance of CI/CIII supercomplexes and abnormal mitochondria with few cristae. 16,17 Moreover giant mitochondria were observed suggesting deficiency of the plant mitochondrial fusion/fission machinery, 16,17 confirming previous results obtained in animals and yeast. [18][19][20] More specifically it was found that CL plays a dominant role in mitochondrial fission through the major mitochondrial fission factor, DYNAMIN-RELATED PROTEIN3 (DRP3).…”
supporting
confidence: 78%
“…16 These reports highlight the central role of CL in maintaining mitochondrial structure and function in yeast, plants, and animals. However, in contrast to yeast crd1 mutant, Atcls seedlings are severely affected, both in their growth and their development, 16,17 suggesting a broader role for CL in plant cell functioning.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, these mitochondria exhibited increased electron density with less and disorganized cristae (Figure 2e), which is in agreement with previously published results. [33][34][35][36][37] In addition to reduction in cyt c, we also observed a decrease in the protein level of MTCO1 (Figure 2b). A reduction in the amount of this labile protein suggests a defect in respiratory chain complex IV assembly.…”
Section: Resultsmentioning
confidence: 70%